Left Ventricular Mass and Volume With Telmisartan, Ramipril, or Combination in Patients With Previous Atherosclerotic Events or With Diabetes Mellitus (from the ONgoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial [ONTARGET]) - Cowan, B.; Young, A.; Anderson, C.; Doughty, R.; Krittayaphong, R.; Lonn, E.; Marwick, T.; Reid, Christopher; Sanderson, J.; Schmieder, R.; Teo, K.; Wadham, A.; et al. (Excerpta Medica, Inc, 2009)
The ONgoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial (ONTARGET) showed that the angiotensin receptor blocker telmisartan 80 mg was not inferior to the angiotensin-converting enzyme inhibitor ramipril 10 mg, and the combination no more effective than ramipril alone, in decreasing morbidity and mortality in patients with cardiovascular disease or high-risk diabetes. Although therapy targeting angiotensin II is known to decrease left ventricular (LV) mass and volume, the relative influence of angiotensin-converting enzyme inhibitor inhibitors and angiotensin receptor blocker, and their combination, on the heart remains unclear in this population. Magnetic resonance imaging was performed in 287 patients enrolled in ONTARGET, across 8 centers in 6 countries, at randomization and after 2-year treatment (90, 100, and 97 patients in the ramipril, telmisartan, and combination therapy groups, respectively). Baseline patient characteristics showed higher frequencies of coronary artery disease, Asian ethnicity, and use of statins and ß blockers than the main ONTARGET trial. LV mass decreased in all groups (p <0.0001 for each), but there were no significant differences in change in LV mass or volume among groups, except that LV mass index decreased more on combination versus telmisartan (p = 0.04). Key determinants of LV mass decrease were a history of hypertension (p = 0.03), baseline mass (p <0.0001), and decrease in systolic blood pressure (p <0.0001). The best magnetic resonance imaging predictor of composite events was end-systolic volume (p <0.0001). In conclusion, telmisartan and ramipril had similar effects on LV mass and volume, and combination therapy was not more effective, in high-risk patients with cardiovascular disease. These results are consistent with the major outcome findings of the main ONTARGET study. © 2009 Elsevier Inc. All rights reserved.